Selling to Wall Street: Theorizing the Financial Commodity Audience in Network Era Television - Peter Arne Johnson (Media Industries)
Although the business-friendly policies and neoliberal ideologies of the 1970s and 1980s certainly accelerated the financialized state of media industries, it is necessary to understand how cultural production has long been subject to the vicissitudes of finance capital. Complementing histories on the role of banking in the formation of the U.S. film industry, this paper explores the interrelationships between finance and a nascent U.S. television industry. Examining trade press discourses and contextualized quantitative data, this case study asks how financialization affected the structures of postwar U.S. broadcasting and the programming and audience targeting of the American Broadcasting Company (ABC) between 1953 and 1964. Rather than simply representing an external force constraining artistic production, the thrust of financialization created a fundamental reorientation of ABC from the inside out. Indeed, during this period, ABC shifted its target audience to, in part, please financial intermediaries but paradoxically alienated those financial elites in the process by turning away from culturally legitimate genres like anthology dramas and high-brow variety series. In charting these continuities and changes, this paper offers a theory of the “financial commodity audience” that helps articulate how financial stakeholders have valued a particular type of viewer: white coastal elites, particularly men. The evidence presented in this case also suggests that cultural industries have been well suited to the extractionary logics of financialization due to the intangibility of their assets and imagined audiences. In this way, media histories remain critical to understanding the power dynamics of financialization and contemporary media industries.